The Closure of the Psychiatric Hospital as an Original Feature of Rehabilitation in Italy. Issue 1 (2nd January 2016) - Ferrannini, Luigi; Peloso, Paolo Francesco
Abstract: In this introduction to a special issue on psychosocial rehabilitation in Italy its context is identified in the closure of psychiatric hospitals since 1978 and in the construction of a system based on community psychiatry and on outpatient services. The particular characteristics of psychiatric rehabilitation in Italy, its strengths and its limitations are then analyzed on different grounds, and some of the key reasons for these limits are then proposed in the evolution of Italian society and in a lack of transformation in the psychiatric identity.